(untitled) (Research, Society and Development, 2022)
The search for a harmonic and aesthetic smile is constant, with an increase in the level of demand and expectation of the patient. Direct veneers in composite resin or indirect veneers in ceramic stand out as a treatment option for rehabilitation, as they are presented as restorative alternatives that mimic the teeth. Address the differences between direct veneers in composite resin and indirect veneers in ceramic, contemplating techniques with and without previous wear and their influence on the longevity and durability of veneers. It consists of a literature review, with searches performed in the following databases: Medline, PubMed and Virtual Health Library (BVS), using the descriptors: dental veneers, ceramic veneers, dental veneers, anterior direct restoration, anterior indirect restoration. A total of 30 studies were selected as the basis for this review. Direct composite resin veneers have advantages such as low cost, less clinical time and excellent aesthetics, as disadvantages they present color instability and high porosity, while indirect ceramic veneers have fracture resistance, durability and longevity as advantages and disadvantages cost. high, requires molding and fragility in handling. To obtain an excellent aesthetic result, professional skill and training are required, as well as the correct execution of restorative techniques, adequate finishing, polishing and maintenance. Both the direct and indirect techniques can be successful, as long as a correct diagnosis, indication and adequate treatment plan are made. Then, there is a need for scientific knowledge, mastery of techniques and skill.